Efektifitas Konseling KBPP dengan Menggunakan Roda Klop dan Leaflet Terhadap Keberhasilan KB Pasca Persalinan di Puskesmas Kotabaru - Novi Sumiani; Nofa Anggraini (Malahayati Nursing Journal, 2024)
ABSTRACT At the Kotabaru Health Center, out of 10 mothers giving birth in March 2023 who received counseling with a clop wheel and leaflets, there were 4 mothers who were willing to take part in postpartum family planning with the MKJP Implant Contraceptive type. (KB Kotabaru Health Center Register March, 2023). Based on this, above, the researcher is interested in conducting research entitled "Effectiveness of KBPP Counseling Using Klop Wheels and Leaflets on the Success of Postpartum Family Planning at the Kotabaru Health Center". To Know the Effectiveness of KBPP Counseling Using Fit Wheels and Leaflets on the Success of Postpartum Family Planning at the Kotabaru Health Center. This study used a quasi-experimental method with a one-group pre-post test design approach. In this design, the researcher intervened in 2 groups. The effectiveness of the treatment was assessed by comparing the pre-test with the post-test. The research population was mothers who gave birth as many as 41 respondents. The research sample consisted of 20 respondents for Roda Klop counseling and 20 samples for counseling with Leaflets at the Kotabaru Community Health Center, bivariate analysis using the Mann-Whitney test. The results of the analysis of the Sig Statistical Test (2-tailed) obtained nilap P – Value = 0.00 (α 0.005) meaning that there is an influence on the effectiveness of the use of postpartum contraception after carrying out Roda Klop counseling at the Kotabaru Health Center, and the results of the Test analysis Sig statistics (2-tailed) obtained nilap P – Value = 0.00 (α 0.005) meaning that there was an influence on the effectiveness of postpartum contraceptive use after Leaflet counseling was carried out at the Kotabaru Health Center. It can be concluded that there is effectiveness of counseling using the Wheel Fit for the success of postpartum family planning and There is effectiveness of counseling using leaflets on the success of postpartum family planning at the Kotabaru Health Center. The recommendation for this research is pregnant women, health workers, educational institutions, and future researchers. Keywords: Postpartum Family Planning Counseling Using Wheel Clops And Leaflets ABSTRAK Di Puskesmas Kotabaru dari 10 ibu bersalin pada bulan maret 2023 yang mendapatkan konseling dengan roda klop dan leaflet terdapat 4 ibu yang bersedia mengikuti KB pasca Persalinan dengan jenis MKJP Kontrasepsi Implan.(Register KB Puskesmas kotabaru Maret,2023).Berdasarkan hal tersebut diatas maka peneliti tertarik untuk melakukan penelitian yang berjudul“Efektifitas Konseling KBPP dengan Menggunakan Roda Klop dan Leaflet Terhadap Keberhasilan KB Pasca Persalinan di Puskesmas Kotabaru”. Diketahuinya Efektifitas Konseling KBPP dengan Menggunakan Roda Klop Dan Leaflet Terhadap Keberhasilan KB Pasca Persalinan Di Puskesmas Kotabaru. Penelitian Ini Menggunakan metoda quasi eksperiment dengan pendekatan one grup pre-post test design ,pada design ini peneliti melakukan intervensi pada 2 kelompok Efektifitas perlakuan di nilai dengan cara membandingkap Pre test dengan post Test .Populasi penelitan adalah ibu yang bersalin sebanyak 41 responden.sample penelitian sebanyak 20 responden untuk konseling Roda Klop dan 20 sample untuk konseling dengan Leaflet di Puskesmas Kotabaru analisis bivariat menggunakan menggunakan uji Mann- Whitney. Hasil analisis Uji Statistik Sig (2-tailed) di dapatkan nilap P – Value = 0.00 ( α 0,005) artinya bahwa ada pengaruh terhadap efektifitas pemakaian alat kontrasepsi pasca persalinan setelah dilakukan konseling Roda Klop di Puskesmas Kotabaru ,dan hasil analisis Uji Statistik Sig (2-tailed) di dapatkan nilap P – Value = 0.00 ( α 0,005) artinya bahwa ada pengaruh terhadap efektifitas pemakaian alat kontrasepsi pasca persalinan setelah dilakukan konseling Leaflet di Puskesmas Kotabaru. Ada efektivitas konseling menggunakan Roda Klop terhadap keberhasilan KB pascasalin dan Ada efektivitas konseling menggunakan Leaflet terhadap keberhasilan KB pascasalin di Puskesmas Kotabaru. Disaran penelitian ini pada ibu hami,tenaga kessehatan ,institusi pendidik,dan peneliti selanjutnya. Kata Kunci: Konseling KB Pasca Persalinan Dengan Menggunakan Roda Klop dan Leaflet